2020
DOI: 10.5502/ijw.v10i1.923
|View full text |Cite
|
Sign up to set email alerts
|

Does team psychological capital predict team outcomes at work?

Abstract: This study is situated in the paradigms of positive organizational scholarship (POS) and positive organizational behaviour (POB). It draws upon the theoretical mechanisms of social learning and emotional contagion to suggest that psychological capital may spread through work teams to impact team outcomes such as performance, innovation, and organizational citizenship behavior (OCB). The degree to which team psychological capital (TPsyCap) mediated the relationship between leader psychological capital (LPsyCap)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 94 publications
1
11
0
3
Order By: Relevance
“…For example, they might be involved in assisting a fellow employee who is behind in his or her job or mentoring new workers. This finding is consistent with that of Waters, Strauss, Somech, Haslam and Dussert (2020) who reported a positive and a statistically significant correlation between PsyCap and OCB.…”
Section: Discussion Of the Resultssupporting
confidence: 92%
“…For example, they might be involved in assisting a fellow employee who is behind in his or her job or mentoring new workers. This finding is consistent with that of Waters, Strauss, Somech, Haslam and Dussert (2020) who reported a positive and a statistically significant correlation between PsyCap and OCB.…”
Section: Discussion Of the Resultssupporting
confidence: 92%
“…Carmona-Halty, Schaufeli, and Salanova (2019) prove that Psycap affects academic performance in the educational field. Other studies revealed that PasyCap is related to career outcomes (Baluku et al, 2021) and organizational citizenship behavior (e.g., Chamisa, Mjoli, & Mhlanga, 2020; Waters et al, 2020). The recent studies also claimed that PsyCap influences innovative behavior (Slatten et al, 2020; Wang, Chen, & Zhu, 2021).…”
Section: Psycap and Performancementioning
confidence: 97%
“…Self-efficacy is considered a powerful individual resource and a part of one's psychological capital (Paterson et al, 2014). Recent work suggests that it can also be generalized to the group level (Waters et al, 2020). Indeed, group efficacy was found to be strongly associated with group member performance in the organizational setting (e.g., Yaakobi & Weisberg, 2018) and in sports (Eys et al, 2019), and individuals and teams in the educational setting (Heled et al, 2016).…”
Section: Perceived Group Efficacymentioning
confidence: 99%
“…Group efficacy may convince individual members that extra efforts and cooperative contributions to the group is worthwhile, because the group is capable of accomplishing its goals. Group efficacy can also be considered as psychological capital from which the member can draw resources when necessary, resulting in increased OCB (Liu et al, 2017; Waters et al, 2020). Indeed, several studies confirmed positive associations between group efficacy and OCB (Chen & Kao, 2011; Lin & Peng, 2010).…”
Section: Perceived Group Efficacymentioning
confidence: 99%